Potential impacts of artificial intelligence for management accounting in the perception of professionals in the field - Marcela Chagas de Souza Schwindt; Simone Alves da Costa (Revista Ambiente Contábil)
Purpose: The objective of this research is to verify the potential impacts that Artificial Intelligence (AI) can have within the field of Management Accounting (MA) in the perception of professionals in the field.